THE EFFECTIVENESS OF USING VIDEO TUTORIAL TO IMPROVING LEARNING MOTIVATION OF CIVIC EDUCATION (Experiment Quasi to Student of SMA Negeri 19 Kabupaten Garut) - Ulpa Dwi Martiani; tetep tetep (Journal Civics and Social Studies, 2019)
The era of globalization has led to the rapid development of science andtechnology, including in the world of education and learning. Civics is one of thesubjects that are still considered saturating, therefore the development of scienceand technology is the supporting force of how civic learning is more interesting.Video tutorial media is one of the effective means to convey the learning messageof Civics. In this study the main objectives that the authors review are themotivation to learn and the use of video tutorial media and their effectiveness inlearning Civics in the SMA Negeri 19 Kabupaten Garut. This research is a quasiexperimental research with One Group Pretest-Posttest Desig research design instudents of class X MIPA 6. The results of hypothesis testing data analysis using ttest tests with (Ha) research is accepted, meaning that if the value of Civic Class Xlessons is more than 70 then there is a significant increase in the effectiveness ofthe use of video tutorials as learning media in increasing students' learningmotivation, reinforced with average test results increased, before using pretestvideo tutorials = 39.80 after the use of posttest = 73.47. Test the correlationcoefficient has a significant relationship with (r) = 0.809 means that the level of therelationship between the two variables "Very High", the coefficient ofdetermination (d) = 65.5% can be said that the use of media video tutorials have aninfluence on increasing student learning motivation as much as The remaining65.5% 34.5% is influenced by other variables. The results of this study concludethat the video tutorial media as a Civics learning media can improve students'learning motivation in SMA Negeri 19 Kabupaten Garut. So that it is expected thatthe teacher can utilize various learning media to improve students' learningmotivation.Keywords: video tutorial, civics learning, learning motivation